Evaluation of employee salary systems through the lens of sharia economic law - Havez, Muhammad; Abdurrahim (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Salary/Wages are payments for services performed by employees within a month. The payroll department plays a crucial role in ensuring company sustainability and preventing payroll fraud. While some employees work solely for financial compensation, others view salary as one of many benefits gained from employment. This study examines the effectiveness of the payroll system at Solah Tampah Hills villa. Method: This study uses a qualitative approach with observation, interviews, and documentation for data collection. The inductive method is applied to analyze empirical field data, which is then interpreted to draw conclusions. Through descriptive analysis and case studies, this research assesses the effectiveness of the payroll system at Solah Tampah Hills villa. Findings: The results of the study indicate that the payroll system at the Solah Tampah Hills villa has been implemented well and is carried out by following the Company Standard Operating Procedures that have been determined by the company. This means that the employee payroll system at the Solah Tampah Hills villa has been running effectively. Conclusion: The study concludes that the payroll system at Solah Tampah Hills villa is effective, as it follows the company's Standard Operating Procedures (SOP). Proper implementation ensures smooth salary distribution and minimizes payroll fraud, contributing to overall business sustainability. Novelty/Originality of this Study: This study provides an in-depth qualitative analysis of the effectiveness of the payroll system at the Solah Tampah Hills villa, highlighting its adherence to SOPs. The research offers a unique perspective on payroll system implementation within the hospitality sector, contributing to the understanding of payroll management effectiveness in business operations.